Distinguishing Pyramid Schemes and Multilevel Marketing - Beasley, Jennifer (My University, 2012)
The number of multilevel marketing organizations has been increasing, and the number of people involved is increasing exponentially. As more people become a part of the multilevel marketing business model, the negative impacts of some multilevel marketing organization practices on people’s lives is growing due to the high potential for moral hazard amongst multilevel marketing organization leadership. It is my contention that new legislation to protect people involved in this type of organization is critical to dramatically reduce the potential for moral hazard. This paper contends that the practices of some multilevel marketing organizations currently can be comparative to pyramid schemes, which is known to have high moral hazard. But the franchise model, which originally had the potential for similar moral hazard, has been greatly reduced through prudent legislation. The ability of this model to minimize the potential for moral hazard maximizes fairness for all parties involved. Therefore, the franchise model guidelines will be examined to provide for a new model for dramatically reducing the potential moral hazard issues posed currently by multilevel marketing organizations.
Keywords: Summa Cum Laude; Finance; University Honors Program